2014
DOI: 10.1038/srep05020
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Composition of Superparamagnetic Iron Oxide Nanoparticles with Various Physico-Chemical Properties and Coatings

Abstract: Because of their biocompatibility and unique magnetic properties, superparamagnetic iron oxide nanoparticles NPs (SPIONs) are recognized as some of the most prominent agents for theranostic applications. Thus, understanding the interaction of SPIONs with biological systems is important for their safe design and efficient applications. In this study, SPIONs were coated with 2 different polymers: polyvinyl alcohol polymer (PVA) and dextran. The obtained NPs with different surface charges (positive, neutral, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
179
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(196 citation statements)
references
References 55 publications
8
179
0
4
Order By: Relevance
“…Transferrin has been frequently identified in the protein coronas of several NPs, for example, silver, iron oxide, and silica. [43][44][45] Here we could identify serotransferrin in the corona of dPGS but not in the corona of dPGOH NPs. Serotransferrin can interact with the transferrin receptor and mediate an endocytotic uptake through clathrin-mediated endocytosis.…”
mentioning
confidence: 63%
“…Transferrin has been frequently identified in the protein coronas of several NPs, for example, silver, iron oxide, and silica. [43][44][45] Here we could identify serotransferrin in the corona of dPGS but not in the corona of dPGOH NPs. Serotransferrin can interact with the transferrin receptor and mediate an endocytotic uptake through clathrin-mediated endocytosis.…”
mentioning
confidence: 63%
“…For PVA-coated SPIONs, the charge of the polymers also influences the protein corona [45] and is different for the three types of PVA-SPIONs (neutral, positively and negatively charged) incubated in FBS for 1 h at 37°C. We also showed there were important differences between in vitro and in vivo protein coronas [28].…”
Section: Importance Of the Protein Corona On Biological Interactionsmentioning
confidence: 99%
“…Experimental approaches used to characterize the PC Many studies have revealed the identity [21,35,38,39,42,[59][60][61] and, more recently, also the quantity [28,36,[62][63][64] of the proteins in the PC using proteomics-based approaches coupled with MS. In a typical experimental plan, NPs are incubated in a biological fluid that ideally should replicate the features of the in vivo biological milieu.…”
Section: New Modelmentioning
confidence: 99%